1. Kementrian Kesehatan Republik Indonesia. Pusat data dan informasi tuberkulosis. Jakarta: InfoDATIN; 2018. 2. Sharma SK, Mohan A, Sharma A. Miliary tuberculosis: A new look at an old foe. J Clin Tuberc. 2016; 3(1):13–27. 3. Ray S. Diagnosis and mana - Anugerah Indah Sari; Roro Rukmi Windi; Hanna Mutiara (CV. Jasa Sukses Abadi, 2019)
Gross motor development is one of children development which must detect in young age for minimize developmental delayed. Age under 3 is a Golden Period which children brain is rapidly develop. Stimulation is a method that can increase children development. Stimulation in age 0-12 month need for optimizing children development. To know mother charactheristic based on giving gross motor stimulation age 0-12 months old at posyandu in Kelurahan Penengahan Raya Kecamatan Kedaton Bandar Lampung. Design of this observational descriptive to 27 mom who had children 0-12 months old at posyandu in Kelurahan Penengahan Raya Kecamatan Kedaton Bandar lampung. The data were taken in the from primary data from questionnaire to score maternal stimulation. We can get mother age 25-35 yo is 18 people and age <25 yo is 9 people. For job distribution, mother who work as housewife is 23 people, enterpreneur is 2 people and employee is 2 people. For last education distribution, elementary is 1 person, JHS is 10 people, SHS is 14 people and collage is 2 people Conclusion: good gross motor stimulation is given by mother who have 25-35 yo, work as housewife and their last education grade is senior high school.